Risk Mitigation and Construction Control for Effective Underwater Recovery of an EPB Shield: A Case Study of the First Metro Tunnel in Tel Aviv. (6th August 2020) - Qi, Weiqiang; Yang, Zhiyong; Jiang, Yusheng; Liu, Zhiyong; Guo, Yinxin; Yang, Xing
Abstract : Shield recovery in water-rich sand strata is a challenging issue in the field of shield tunnel engineering, especially when the end of the shaft cannot be reinforced by jet grouting or freezing or when the shield cannot be supported with a steel sleeve. Therefore, it is important to develop an effective recovery approach and adopt suitable techniques to control the risks. In this study, a new method based on filling the receiving shaft with water is proposed for the underwater recovery of an earth pressure balance (EPB) shield with zero end reinforcement from a metro tunnel in Tel Aviv, Israel. Several additional techniques are used to ensure safe recovery of the shield, including the design of a concrete cradle, drilling of pressure relief holes, control of excavation parameters, screw conveyor sealing, portal sealing, tail sealing, and grouting. Furthermore, according to the actual situation on site, filling the shaft with water to 1 m above the water level in the strata can prevent the fine sand from percolating into the shaft. Before the cutterhead approaches the underground diaphragm wall, the driving attitude should be strictly controlled, and the edge hob should be inspected for wear. The necessary thrust of shield tunneling in the underground diaphragm wall and shaft is calculated theoretically. In order to ensure the deformation control of the underground diaphragm wall and the smooth tunneling of the shield, the thrust of the shield excavating the underground diaphragm wall will not be larger than 12 000 kN, and the penetration degree will be limited to 3 mm/ r . Qualitative observations and measurements of surface subsidence in the metro tunnel indicate that these risk mitigation techniques are effective and suitable for the underwater recovery of EPB shields in water-rich sand strata.